2018
DOI: 10.3126/banko.v27i3.20557
|View full text |Cite
|
Sign up to set email alerts
|

Towards active utilisation of community forestry: Silvo-institutional model for sustainable forest management in Nepal

Abstract: This paper explains what we term the 'silvo-institutional model' for a more productive, sustainable and equitable management of community forests in Nepal. The paper draws on four years of action research in six research sites of Kavre and Lamjung districts, complemented by the review of silviculture-based forest management by Government of Nepal in various parts of the country. The findings indicate that first, early silviculture-based forest management initiatives have failed because they did not adequately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Though this management requires substantial engagement of the users, user ranked decreased user involvement after SciFM as a second (28%) among the factors (Figure 3). This supports the argument of Paudel et al (2018), who claims that scientific forest management implementation requires complex and more technical knowledge that will decrease the participation of users in the decision-making process. In the same line, one of the CFUG committee members explained that:…”
Section: Social Criteriasupporting
confidence: 80%
See 1 more Smart Citation
“…Though this management requires substantial engagement of the users, user ranked decreased user involvement after SciFM as a second (28%) among the factors (Figure 3). This supports the argument of Paudel et al (2018), who claims that scientific forest management implementation requires complex and more technical knowledge that will decrease the participation of users in the decision-making process. In the same line, one of the CFUG committee members explained that:…”
Section: Social Criteriasupporting
confidence: 80%
“…Several scholars present opposing arguments regarding different aspects of SciFM implementation. For instance, Paudel et al (2018) label it as a "program" in the name of active utilization implemented without considering institutional aspects. They argue about its outcomes claiming that outcomes are limited on the ground.…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, EnLiFT developed the Silvo-Institutional Model (SIM) in which the technical aspects of resource assessment, demonstration plots, felling and timber distribution are combined with institutional aspects of consultation, developing governance safeguards and preparing the required documentation correctly (Cedamon et al 2017a;Paudel et al 2018). This approach built on earlier work on collaborative learning (McDougall et al 2007) and deliberative scientific practice (Ojha et al 2010).…”
Section: Silvo-institutional Model For Scientific Forest Managementmentioning
confidence: 99%
“…For example, a 2016 study in the Koshi Hills found that a hundred of the 144 forestryrelated enterprises were NTFP-related (Rai et al 2006). The government's singular focus on forest conservation for decades has meant that, until recently, there has been little interest in appropriate forms of silvicultural management to support CFEs engaged in the timber and other wood product industries (see Paudel et al 2019).…”
Section: Emergence and Growth Of Communitymanaged Forest Enterprisesmentioning
confidence: 99%